Identification and Validation of Reference Genes for RT-qPCR Normalization in Mythimna separata (Lepidoptera: Noctuidae). (31st July 2018) - Li, Ke; Xu, Na; Yang, Yu Jing; Zhang, Jin Hui; Yin, Huan
Abstract : Mythimna separata is a major agricultural pest with seasonal migrating trait in China. Formation and regulation mechanism of migration behavior has resulted in a large number of fundamental researches involving quantitative studies of gene expression in this species. Using appropriate reference gene is critical in RT-qPCR data normalization. A comprehensive study on the reference genes in M. separata is lacking. In this paper, expression stabilities of ten candidate reference genes were evaluated in M. separata under various biotic and abiotic conditions by employing four different software geNorm, NormFinder, BestKeeper, and the comparative ΔCT method. The comprehensive stabilities ranking of these genes were suggested by RefFinder. PKG as a target gene was employed to justify the number of reference genes in four larval tissues and two photoperiod treatments. Results demonstrate that the first three most stable genes were as follows: EF, CypA, and β -TUB for developmental stages; EF, CypA, and RPL12 for larval tissues; EF, TBP, and β -TUB for adult tissues . RPL12, β -TUB, and EF for densities; EF, RPL12, and GAPDH for photoperiod treatments; β -TUB, EF, and ATPase for temperature treatments. Stable reference gene combinations may reduce bias in normalization. This work provides for the first time a comprehensive list of appropriate reference genes and facilitates future studies on gene function of M. separata.